جريمت الإتجار بالأعضاء البشريت في ظل قاوىن العقىباث الجزائري - بوعوينة وفاء * * بلمانع حسن (المسيلة, 2022)
لم يتطرق المشرع الجزائري إلى بعض عمليات إستغلال الأعضاء البشرية كإستئجار الرحم وتنظيم بنوك الأعضاء البشرية؟ لم يتطرق المشرع الجزائري إلى تنظيم بعض أنواع عمليات الزرع التي خلقت إشكاليات قانونية وإجتماعية ودينية كزرع الأعضاء التناسلية؟ لم يعرف العضو البشري ولا إلى تعريف الإتجار بالأعضاء البشرية؟ عدم إضافة عبارة (أو شرع في ذلك) بالنسبة لجنحة التبليغ عن جنحة الإتجار بالأعضاء البشرية كون أن المشرع عاقب على الشروع في الإتجار بالأعضاء موازاة مع الجريمة التامة لها وكان من الأجدر أن ينصب العقاب أيضا على عدم التبليغ في حالة الشروع كونه أولى بالعقاب أيضا نظرا للطابع الوقائي والإستعجالي للعملية التي من شأنها الوقاية من وقوع الفعل الإجرامي أصلا ؟ وختاما نرجو أن يتم تدارك هذه النقائص في التعديلات المستقبلية وذلك لتحقيق فعالية ونجاعه أكبر في محاربة هذه الجريمة الحديثة والخطيرة جدا. Summary Did the Algerian legislator not address some of the operations of exploiting human organs, such as renting the womb and organizing human organ banks? Did the Algerian legislator not address the regulation of some types of transplants that created legal, social and religious problems such as genital transplantation? He did not know the human organ, nor to the definition of trafficking in human organs? Not to add the phrase (or attempted to do so) with regard to the misdemeanor of reporting the misdemeanor of trafficking in human organs, since the legislator penalized the attempt to trade in organs in parallel with the complete crime thereof. Preventive and urgent process that would prevent the occurrence of the criminal act in the first place? In conclusion, we hope that these shortcomings will be rectified in future amendments in order to achieve greater effectiveness and efficiency in combating this modern and very dangerous crime
Keywords: الجريمة-الإتجار بالأعضاء البشرية--قاوىن العقىباث الجزائري